(untitled) (AYUSHDHARA, 2024)
Knee is one of the largest and most complex joint of body. The complexity is because where there will be fusion of Lateral femorotibial, Medial femorotibial and Femoropatellar joints. Here a case report of 24 years female while playing had a sudden trauma to right knee with severe pain and swelling. Patient was unable to flex the knee joint. On MRI she was diagnosed with thinning and altered signal intensity of anterior cruciate ligament with partial tear and thickening of the medial meniscus with horizontal tear in posterior horn. By this patient was unable to do day to day activities. Here 2 months of Ayurvedic treatment was followed by patient who provided relief from pain and brought a significant improvement in the movement of knee joint.